Liposomes for systematic delivery of vancomycin hydrochloride to decrease nephrotoxicity: Characterization and evaluation - Junli Liu; Zhonglan Wang; Fubing Li; Jinhua Gao; Longmei Wang; Guihua Huang (Elsevier, 2015)
Vancomycin hydrochloride （VANH）, the first glycopeptide antibiotic, is a water-soluble drug for the treatment of acute osteomyelitis. Liposomal formulations of VANH have already been manipulated and characterized, which was a mean of increasing their therapeutic index, reducing their toxicity and altering drug biodistribution. One of the challenges for preparing VANH-Lips is their low encapsulation efficiency (EE). In the present study, we aim to improve the liposomal formulation of VANH for higher EE, longer systemic circulation, reduced nephrotoxicity and enhanced antimicrobial activities. Vancomycin hydrochloride-loaded liposomes (VANH-Lips) were formulated by the method of modified reverse phase evaporation. Based on the optimization of formulation with orthogonal experimental design, the average drug encapsulation efficiency and the mean particle size of VANH-Lips were found to be 40.78 ± 2.56% and 188.4 ± 2.77 nm. In vitro drug release of VANH-Lips possessed a sustained release characteristic and their release behavior was in accordance with the Weibull equation. After intravenous injection to mice, the mean residence time (MRT) of VANH-Lips group was significantly prolonged in vivo and the AUC value was improved as well compared with the vancomycin hydrochloride solution (VANH-Sol) group. Furthermore, the biodistribution results in mice showed that VANH-Lips decreased the accumulation of VANH in kidney after intravenous injection. In conclusion, VANH-Lips may be a potential delivery system for VANH to decrease nephrotoxicity in the treatment of osteomyelitis.